Disclosure of Islamic Social Reporting in Indonesian Islamic Banking: Comparative Analysis of Islamic Commercial Banks for the Period 2019–2023 - Eni Haryani Bahri; Marfuah; Munadiati (Jurnal Investasi Islam, 2025)
CSR in the conventional perspective is disclosed using the Global Reporting Initiative (GRI) index, while CSR disclosure in the Islamic perspective uses Islamic Social Reporting. This study aims to analyze the disclosure of the ISR Index at Indonesian Sharia Commercial Banks for the period 2019-2023. The method used in this study is comparative qualitative with content analysis based on the concept of Shariah Enterprise Theory (SET). Based on the results of the study, overall, when viewed from the Islamic Social Reporting (ISR) Index, the level of disclosure carried out by each Islamic bank varies, indicating the company's ability to provide the best performance for the community. At Bank Syariah Indonesia, ISR disclosure has increased significantly since 2021, with an average ISR value of 92% in 2023, indicating highly informative disclosure. Bank Aceh Syariah remained stable at around 73–89%, which is typical for smaller regional banks with concise sustainability reports. Bank Muamalat scored lower, between 72–85%, but showed consistent and fairly comprehensive ISR disclosure. The corporate governance theme tends to have the highest score, while the environmental theme has the lowest score among the three banks, although it continues to improve every year. Disclosure scores are classified into the following categories: Very Informative (81-100).